А Well-Founded Method of Treatment of Children with Perinatal Damage to the Nervous System (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Magnesium is the second most important intracellular element in the body. About 20% of magnesium is in muscle tissue, the remaining 20% is in the blood and other tissues of the body. 93 children of the first year of life were examined, who had manifestations of perinatal damage to the nervous system against the background of the underlying disease. Magne B-6 was administered orally once a day at a dose of 6-8 mg / kg of body weight. The criterion of effectiveness was the clinical improvement of the condition of patients, reduction of intracranial hypertension, improvement of sleep, acceleration of the pace of psychomotor development.